B. AS IN BALKAN: TERÉZIA MORA'S POST‐YUGOSLAV BERLIN REPUBLIC*. (April 2014) - Mayr, Maria
ABSTRACT In this article, I argue that Terézia Mora's 2004 novel Alle Tage foregrounds the Yugoslav wars, and the Kosovo intervention in particular, as significant events for processes of the Berlin Republic's political self‐fashioning in the late 1990s. I therefore contend that despite the text's more widely acknowledged global and delocalised aspects, Alle Tage is in fact a very local and 'German' text, directly engaging with the socio‐political contexts of the Berlin Republic. I start by addressing the ways in which the 1990s Balkan wars have been used to reposition questions of German identity in relation to its World War II past. I then examine and offer an alternative to the notion that Térezia Mora's novel Alle Tage is predominantly a global text by highlighting the text's inextricable embeddedness in discourses surrounding German identity in the 1990s. I do so by tracing the novel's simultaneous critiques of both the notion of a global, nomadic way of being as well as of essentialist conceptions of community such as a nation or ethnic belonging. As the fate of the novel's main character Abel illustrates, for Mora belonging is instead a matter of an embodied, experiential access to both one's past and present. I conclude by arguing that Mora's novel suggests that just like Abel, Germany cannot move beyond post‐war themes such as nationalism, war, and genocide without thereby committing violent acts of forgetting.